Snow, Thaw, Temperature, and Permafrost Borehole Data from Lake Colleen and Airport Study Sites, Prudhoe Bay, Alaska, 2016 - Donald A. Walker; Mikhail Kanevskiy; Martha Raynolds; Yuri L. Shur; Marcel Buchhorn; Ksenia Ermokhina; Lisa Druckenmiller; Jana L. Peirce (Arctic Data Center, 2018)
This data report contains methods and data from transects, permanent vegetation plots, and boreholes sampled in March and August-September 2016 at Colleen Site A and the Airport Study Site, Prudhoe Bay, Alaska, for the Arctic Science, Engineering, and Education for Sustainability (ArcSEES) program. The ArcSEES project, "Cumulative effects of Arctic oil development—planning and designing for sustainability," was funded by the National Science Foundation (NSF Grant Nr. 1263854). The study sites consists of three 100-meter (m) transects established near the Deadhorse Airport and two 200-m transects near Lake Colleen. This builds on data collected in 2014 and 2015. In 2016, snow depth, thaw depth, temperature and permafrost borehole data were collected along transect flag lines and at permanent vegetation plots established at polygon centers and troughs at intervals along transects. The data report also includes 41 photos of the disturbance to the tundra caused by installation of the Quintillion terrestrial fiber optic cable along the Dalton Highway in 2015-2016. More info: http://www.geobotany.uaf.edu/arcsees/